Synthesis and activity of a novel inhibitor of nonsense-mediated mRNA decay. Issue 5 (7th January 2016) - Gotham, Victoria J. B.; Hobbs, Melanie C.; Burgin, Ryan; Turton, David; Smythe, Carl; Coldham, Iain
Abstract : A new route to a tetracyclic lactam was developed and the product, calledVG1, was found to inhibit nonsense-mediated mRNA decay at μM concentrations. Abstract : During efforts to prepare the known compoundNMDI1, a new tetracyclic compound, calledVG1, was prepared in six steps. This compound was found to have good activity as an inhibitor of nonsense-mediated mRNA decay.